Analysis of Crystallinity and Morphology of Bacterial Cellulose/Chitosan Based Composite Film - Baihaqi Mukhammad Fisni; Suryanto Heru; Aminnudin Aminnudin; Puspitasari Poppy; Maulana Jibril; Nusantara Fajar; Renandito Muhammad Pramudya; Osman Azlin Fazlina; Yanuhar Uun (BIO Web of Conferences, 2025)
Pineapple peel can be effectively utilized in fermentation process to produce bacterial cellulose (BC). This study uses pineapple peel extract to produce BC, combined with chitosan to form composite films. The study aims to analyze the crystallinity and investigate the surface morphology of BC film with chitosan reinforcement. This method includes the cellulose synthesis through the fermentation process, alkalization, and defibrillation using high-pressure homogenization on BC and the synthesis of BC film with chitosan content of 2.5%, 5%, 7.5%, and 10% then casting and drying at 50°C for 20 hours. Crystallinity was analyzed using X-ray diffraction, and surface morphology was observed using a scanning electron microscope. Results showed an influence of adding chitosan on the surface morphology and crystallinity of the BC composite film. The diffraction pattern indicates dominant peaks with the addition of chitosan were achieved at about 11°, 14°, 16°, 22°, and 26°. The addition of chitosan reduces the crystallinity index of BC film from BC Control 83.4 % to 75.4% after adding chitosan of 10%. Surface morphology shows a smooth surface of film on BC film, but rougher after adding chitosan to make the surface corrugated. Future studies will explore the benefits of film in biopackaging applications.